2019
DOI: 10.3390/ani9060310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein Restriction on Performances and Meat Quality of Cinta Senese Pig Reared in an Organic System

Abstract: In lean genotypes, protein restriction during growing increases intramuscular fat content without affecting the overall carcass fatness. The present study aims to assess the feasibility of applying this feeding management on an obese pig, the Cinta Senese, since obese genotypes are characterized by great lipogenic potential often leading to excessively high backfat deposits. Twenty pigs of average weight 38 kg, were divided in two groups, the first group was fed a protein restricted diet (9% of crude protein),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
(65 reference statements)
7
6
0
Order By: Relevance
“…Trimming, the procedure that removes rind and external fat in the traditional V-shape, facilitates the salting phase and standardizes the subcutaneous fat thickness [ 36 ]. However, no significant effect of diet was observed as regards the final weight and yield of trimmed hams, in accordance with others studies carried out in Cinta Senese [ 10 ] and Large White × Landrace [ 7 ] pigs, respectively. This is important because ham is the main dry-cured product obtained from Iberian pigs, characterized by its high sensory quality and high price in the market [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Trimming, the procedure that removes rind and external fat in the traditional V-shape, facilitates the salting phase and standardizes the subcutaneous fat thickness [ 36 ]. However, no significant effect of diet was observed as regards the final weight and yield of trimmed hams, in accordance with others studies carried out in Cinta Senese [ 10 ] and Large White × Landrace [ 7 ] pigs, respectively. This is important because ham is the main dry-cured product obtained from Iberian pigs, characterized by its high sensory quality and high price in the market [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, feeding pigs on low-protein diets is a tool not only to reduce feed costs, nitrogen excretion, and gut health, but also could contribute to improving meat quality without affecting pig production performance. In this sense, several studies have been carried out to explore the effect of different nutritional strategies, based on reducing crude-protein content [ 5 , 6 , 7 , 8 , 9 , 10 ], essential amino acids levels, such as lysine [ 11 , 12 , 13 , 14 , 15 ], or both of these [ 16 ] in the diet, on growth performance, carcass composition, and meat quality of pigs. It is well known that a high amount of intramuscular fat (IMF) is one the most relevant aspects of meat quality [ 17 ], and although low-fat pork could be interesting for reducing caloric intake in humans, an IMF level below 2.5% is related to lower sensory meat quality [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…No differences in carcass yield were found in our work, in accordance with previous results in Iberian pigs [26] and in other pig breeds [35,39]. In contrast, Rey et al [40] found higher carcass yield in pigs fed in confinement than in those fed under free-range conditions with acorn and grass, probably due to the greater fiber content in grass compared to concentrate diet, which could increase the development of the digestive system (mainly large intestine), as evidenced Roskosz et al [41] in wild pigs fed on diets with a high cellulose content.…”
Section: Pig Performance and Carcass Quality Traitssupporting
confidence: 93%
“…However, the higher feed intake of intensively reared pigs increased the gut fill [19], which could compensate for the greater development of the digestive system from free range-reared pigs. Related to dietary protein content, our results are in agreement with previous papers [35,42], indicating that it is possible to reduce dietary crude protein without affecting growth performance and carcass composition as long as daily amino-acid supplies are adequate [34]. Only in loins were significantly lower levels of weight and yield detected in FR than in SP pigs, with intermediate values in LP.…”
Section: Pig Performance and Carcass Quality Traitssupporting
confidence: 91%
See 1 more Smart Citation